2009
DOI: 10.1172/jci38575
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate in the plasma compartment regulates basal and inflammation-induced vascular leak in mice

Abstract: Maintenance of vascular integrity is critical for homeostasis, and temporally and spatially regulated vascular leak is a central feature of inflammation. Sphingosine-1-phosphate (S1P) can regulate endothelial barrier function, but the sources of the S1P that provide this activity in vivo and its importance in modulating different inflammatory responses are unknown. We report here that mutant mice engineered to selectively lack S1P in plasma displayed increased vascular leak and impaired survival after anaphyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
273
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 248 publications
(291 citation statements)
references
References 46 publications
14
273
1
3
Order By: Relevance
“…8,14,38 A recent study using sphingosine kinases-null mice indicated that plasma S1P is required for vascular integrity. 16 Furthermore, administration of synthetic S1P 1 agonists, which powerfully induce downregulation of S1P 1 , but also that of S1P 1 antagonists induced pulmonary edema. 15,17,39 Therefore, S1P 1 seems to maintain vascular integrity in a tonic manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,14,38 A recent study using sphingosine kinases-null mice indicated that plasma S1P is required for vascular integrity. 16 Furthermore, administration of synthetic S1P 1 agonists, which powerfully induce downregulation of S1P 1 , but also that of S1P 1 antagonists induced pulmonary edema. 15,17,39 Therefore, S1P 1 seems to maintain vascular integrity in a tonic manner.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Different from S1P 2 , S1P 1 maintains not only constitutive barrier integrity but protects against barrier disruption caused by anaphylaxis and inflammation. 15,16,39 It is likely that S1P 1 protects the integrity of AJ through a mechanism different from eNOS-NO regulation. Thus, these observations together with the previous Cui 21 observations 27 suggest that receptor signaling mediated by G q/11 , G i and G 12/13 play distinct critical roles in triggering, preventing and limiting vascular leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of anti-S1P antibody is substantial and more than that obtained 16 with monoclonal anti-VEGF antibody. This anti-tumor effect is likely due to inhibition of both angiogenesis and tumor cell motility, survival and proliferation [44].…”
Section: Regulation Of Vascular Formation By S1p Receptor Signalingmentioning
confidence: 94%
“…In addition, animal studies suggest that targeting the S1P signaling system is a promising strategy for inhibiting vascular hyperpermeability and modulating angiogenesis [13,15,16]. Here, we will overview the signaling mechanisms underlying S1P regulation of biological functions 5 and the roles of S1P in diseases.…”
Section: Introductionmentioning
confidence: 99%